Overview of digital locks with artificial intelligence - Lvov, А. А.; Sotnik, S. V. (ХНАДУ, 2024)
This study presents a comprehensive review of digital locks incorporating artificial intelligence. The research focuses on analyzing four models: Philips Easy Key Alpha, Philips Easykey DDL702E, Philips Easykey7300, and Kaadas K9 Black. Key characteristics, advantages, and disadvantages of each lock were examined to provide insights for selecting best option for home security. The analysis revealed that while all models ensure high security and convenience through diverse access methods (fingerprints, codes, smartphones), they share limitations such as battery dependency and higher costs compared to traditional locks. The findings aim to guide consumers in making informed choices based on their specific needs and priorities, laying the groundwork for designing advanced AI-powered locks in future.
Keywords: Digital locks; advanced security features; real-time monitoring; remote access; adaptive algorithms; user data privacy; access control systems; smart home; mobile app control; keyless entry; cybersecurity; machine learning; voice recognition; facial recognition